Estágio curricular supervisionado na Licenciatura plena em Química e a Integração Teoria e Prática: perspectivas do constituir-se professor - Sousa, Roselene Ferreira (2017)
The objective of this research was to understand the role played by the Supervised Internship of the FECLESC / UECE Chemistry Degree and its effectiveness in the spaces of the University and the Basic School, analyzing the conceptions of the pedagogical agents involved, considering the perspective of the unit Theory and Practice in teacher education. The study using the qualitative approach is descriptive in the data analysis. As a methodology, the case study was chosen and the data collection instruments were documental analysis and semistructured interviews. Initially the possibilities of the research were tested with a literature review, bringing together authors for the theoretical basis of the study. An exploratory visit was then made to select the faculty, the schools and the subjects participating in the research, selected according to established criteria such as location of the faculty and schools, receptivity of the directors and teachers, formation Teacher's time of service. One college, two schools, two faculty members and two teachers from two elementary schools where the Supervised Internship develops have met the established criteria and have therefore been chosen. With the insertion in the field, faculty, schools and teachers were characterized for the purpose of identifying the environment and research subjects. It can be considered that FECLESC / UECE's Supervised Internship, especially in the Degree in Chemistry, was constituted, going through many difficulties, manifesting conceptions, ideologies and experiences of each instructor of the internship, since there was no systematization at the beginning of the course. The research also showed that the guidelines prescribed in the official and institutional documents currently in force for the development of the Supervised Internship, propose a conception of the internship in a critical and reflective perspective. In the conceptions of the subject teachers of the research, the stage is important, it is the moment of the student being before the reality of the teaching profession. However, at that moment, the ideology, culture and experience of each subject are manifested, since each one performs his work within the process, each one tries to conform to the regulatory norms systematized in official and institutional documents, that is, Each one develops its role in direct confrontation between the official curriculum, its culture and conceptions.